CRISPR-based systems for sensitive and rapid on-site COVID-19 diagnostics. Issue 11 (November 2022) - Soh, Jun Hui; Balleza, Enrique; Abdul Rahim, Muhammad Nadjad; Chan, Hsi-Min; Mohd Ali, Siswand; Chuah, Jacqueline Kai Chin; Edris, Sherif; Atef, Ahmed; Bahieldin, Ahmed; Ying, Jackie Y.; Sabir, Jamal S.M.
Abstract : The COVID-19 pandemic has strained healthcare systems. Sensitive, specific, and timely COVID-19 diagnosis is crucial for effective medical intervention and transmission control. RT-PCR is the most sensitive/specific, but requires costly equipment and trained personnel in centralized laboratories, which are inaccessible to resource-limited areas. Antigen rapid tests enable point-of-care (POC) detection but are significantly less sensitive/specific. CRISPR-Cas systems are compatible with isothermal amplification and dipstick readout, enabling sensitive/specific on-site testing. However, improvements in sensitivity and workflow complexity are needed to spur clinical adoption. We outline the mechanisms/strategies of major CRISPR-Cas systems, evaluate their on-site diagnostic capabilities, and discuss future research directions. Highlights: CRISPR-based detection systems are poised to emerge as the next-generation point-of-care (POC) diagnostic platform, and have the potential to marry the advantages of RT-PCR (sensitive/specific) and rapid test kits (RTKs) (fast turnaround, user-friendly). These systems also circumvent the deficiencies of both RT-PCR (long turnaround, equipment/trained user requirement) and RTKs (low sensitivity). These POC platforms play a crucial role for effective medical intervention and transmission control of infectious diseases such as COVID-19. For these systems to be widely adopted clinically, developments have been made to enhance the thermal compatibility of CRISPR with isothermal amplification assays, towards a one-step, one-pot platform.